2011
DOI: 10.1209/0295-5075/95/31002
|View full text |Cite
|
Sign up to set email alerts
|

Holographically smeared Fermi surface: Quantum oscillations and Luttinger count in electron stars

Abstract: We apply a small magnetic field to strongly interacting matter with a gravity dual description as an electron star. These systems are both metallic and quantum critical at low energies. The resulting quantum oscillations are shown to be of the Kosevich-Lifshitz form characteristic of Fermi liquid theory. It is seen that only fermions at a single radius in the electron star contribute to the oscillations. We proceed to show that the Fermi surface area extracted from the quantum oscillations does not obey the si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 59 publications
4
76
0
Order By: Relevance
“…The challenge for the future is to describe the phases of Sections V and VI using the dual gravity theory, in a manner which captures their expected properties of finite-range models in d = 2 and d = 3 respectively, and there have been recent studies in this direction [10,[12][13][14][15][16][17][18]20]. In particular, the d = 3 model of Gubser and Rocha [10] is a promising model for future study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenge for the future is to describe the phases of Sections V and VI using the dual gravity theory, in a manner which captures their expected properties of finite-range models in d = 2 and d = 3 respectively, and there have been recent studies in this direction [10,[12][13][14][15][16][17][18]20]. In particular, the d = 3 model of Gubser and Rocha [10] is a promising model for future study.…”
Section: Discussionmentioning
confidence: 99%
“…An analogy with the Fermi gas at unitarity helps clarify this point: this theory contains a composite boson which can be either canonical or non-canonical, and the choice only distinguishes different perturbative expansions of the same physics. [51,52] Also, with attractive gauge forces between the b± bosons and f ± fermions, we can expect that they form multiple bound states, and each of these lead to separate Fermi surfaces: in particular, this expected from the multiple Fermi surfaces seen in a recent holographic analysis [14,15]. For simplicity, we will only consider a single such bound state, and a single c fermion here, but it is not difficult to extend our analysis to multiple c fermions.…”
Section: Theory Similar To the Abjm Model In D =mentioning
confidence: 98%
See 1 more Smart Citation
“…(7.6). A number of recent theories [75][76][77][78][79][80][81][82][83][84] have examined the feedback of the finite density matter on the metric of the AdS space, and found that the AdS 2 horizon disappears at T = 0, and is replaced by a metric with a finite value of z. Many physical properties of such holographic metals are similar to those of the field theory in Eq.…”
Section: A Connections To Holographic Metalsmentioning
confidence: 99%
“…In [9][10][11], it was pointed out that a holographic system with a charged bulk fermion, which is called "electron star" in the literature, exhibits the Luttinger theorem of the boundary fermion theory. This is based on the observation that the bulk fermions obey a bulk Luttinger theorem at each radius for the electron star.…”
Section: Jhep07(2012)064mentioning
confidence: 99%